Physical Activity and Smoking Habits are Closely Related to Cardiovascular Endurance in Farmers - Wiatma, Deny Sutrisna; Samoedra, Reksa; Saputra, I Putu Bayu Agus; Setia, Bayu (Indonesian Journal of Global Health Research, 2024)
In 2019, there were 523 million cases of cardiovascular disease which caused the deaths of 18.6 million people. In this manner, some major issue should be considered, high cardiovascular endurance, for example. Relatively, high cardiovascular endurance can reduce the incidence of cardiovascular disease by 40% to 70%. Objective to nalyzing the relationship between physical activity and smoking habits among farmers in Pandan Wangi Village. The method used is quantitative research with cross-sectional design involving 108 respondents. The respondents were selected by a simple random sampling technique. Data in this study were collected using GPAQ for physical activity variables, Brinkman index questionnaire for smoking variables, and Harvard step test for cardiovascular endurance variables. Meanwhile, Spearman rank test was used in the data analysis. The research shows that the characteristics of respondents were dominated by male (64.8%) within 36-45 years old age range group (52.8%). In addition, most of the respondents were non-smoker category (62.0%), had a high level of physical activity (52.8%), and a very good level of cardiovascular endurance (27.8%). Bivariate analysis shows that there is a significant relationship between physical activity (p-value = 0.005) and smoking behavior (p-value = 0.047) on cardiovascular endurance among farmers in Pandan Wangi Village. There is a significant relationship between physical activity and smoking habits on cardiovascular endurance among farmers in Pandan Wangi Village.